Virtual Humans in Drug Development: Integrating Digital Models with Pharmacological Science - Mohamed Afsal A; Dhivya G; Gowrishallini P; Devi Sowndarya N; Suprraja S (Asian Journal of Pharmaceutical Research and Development, 2025)
The conventional pathway of drug development is laborious, costly, and laden with high attrition rates. Recent advances in computational biology have spotlighted the potential of virtual human models, also known as in-silico human avatars, to revolutionize pharmacological research. This review aims to explore the potential of these digital tools in transforming drug discovery and development.These computer-generated, physiology-based simulations replicate biological systems and offer a safe, cost-effective, and ethical alternative for drug testing and disease modeling. In-silico pharmacology allows researchers to perform complex simulations of pharmacokinetics (PK), pharmacodynamics (PD), toxicity, and drug-disease interactions using virtual models that emulate human anatomy and physiology. This approach is increasingly valuable given the ethical constraints of animal testing and the need for accelerated drug discovery timelines. The development of digital twins, which represent the virtual counterpart of real patients, further empowers precision medicine and individualized therapy selection. By integrating artificial intelligence (AI), machine learning (ML), and physiologically based pharmacokinetic (PBPK) models with these avatars, predictive accuracy and the personalization of therapeutic strategies are significantly enhanced.This review discusses the core components, applications, challenges, and regulatory landscapes surrounding virtual human models in drug development.